Calling an audible: COVID-19 and competitive sports - Nallamothu, B. K. (Circulation, 2020)
In this issue of Circulation: Cardiovascular Quality & Outcomes, we publish a Cardiovascular Perspective by the Big Ten Cardiac Registry Steering Committee (CRSC). The article details a series of key recommendations made by this committee of conference administrators and physicians from diverse specialties including cardiology in light of the coronavirus disease 2019 (COVID-19) pandemic. It reviews the overall timeline of critical events that led initially to the cancellation of spring and fall sports as well as the recent decision by the Big Ten to allow football (and presumably other fall sports) to proceed. Challenges faced by the Big Ten CRSC during their deliberations and their latest reversal are not unlike those faced by groups in other fields. Decisions about when to close and re-open activities have shifted over time with accumulating data on the overall risks of COVID-19. Gauging such risks had been hard initially for sports like football that could not ensure safe social distancing. But with accumulating data in recent weeks from conferences that proceeded with playing football as well as other sports, the feasibility and safety of protocols for potentially minimizing the dangers of COVID-19 became clearer. Of course, making the right decision is crucial. It has implications not just for the student athletes and coaches involved but for the communities in which these individuals live and work. I hope that you will find this article interesting and a valuable read. It may help you better appreciate the enormous complexity encountered by the Big Ten CRSC in forming their recommendations as well as the inherent tradeoffs they had to weigh while relying on imperfect information. Their conclusions admittedly do not represent definitive science. That would be difficult to achieve given the evolving stage we are currently in with the COVID-19 pandemic. Instead, these conclusions demonstrate how limited scientific findings may often intermingle with broader societal values in balancing the risks and benefits of any policy.